2003
DOI: 10.1891/cmaj.4.1.53.57471
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s Disease Caregiving: Implications for Care Management

Abstract: The primary objective of this study was to identify the needs of caregivers of individuals with Parkinson's disease within the context of the common functional, memory, and behavioral problems experienced by Parkinson's patients. A second objective was to evaluate any differences between caregivers of Parkinson's patients and caregivers of adults with other forms of cognitive impairment. Data used for this analysis were collected in 1999, by the 11 Caregiver Resource Centers that form California's statewide Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…This is in agreement with other studies comparing family caregivers of persons with PD with other family caregivers where it was noted that those who care for patients with PD 'demonstrated increased depression and other health conditions'. 30 To ease caregiver burden, Caap-Ahlgren and Dehlin 31 counsel paying attention to the functional status of the patient and to indicators of the depressive state of the caregiver.…”
Section: Care Givingmentioning
confidence: 99%
“…This is in agreement with other studies comparing family caregivers of persons with PD with other family caregivers where it was noted that those who care for patients with PD 'demonstrated increased depression and other health conditions'. 30 To ease caregiver burden, Caap-Ahlgren and Dehlin 31 counsel paying attention to the functional status of the patient and to indicators of the depressive state of the caregiver.…”
Section: Care Givingmentioning
confidence: 99%
“…Table 4 summarizes data from our evaluation of key recent international studies of PD caregiver strain. The results show world-wide data demonstrating that care-giver strain is challenging and common, with many shared features between south-east Asia and other regions of the globe, as seen in the world-wide literature ( 40 79 ).…”
Section: Resultsmentioning
confidence: 56%
“…Regardless of geographical, cultural, and geopolitical differences, caregiver strain in PD is a major problem world-wide and correlates with disease severity ( 40 79 ). Our study showed that most south-east Asian PD caregivers are family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This neurodegenerative disease manifests itself particularly in persons over the age of 65 (Alves, Forsaa, Pedersen, Dreetz Gjerstad, & Larsen, 2008). Of these, 90% live at home, and most are cared for by an elderly spouse (Parrish, Giunta, & Adams, 2003). It is usually at the moderate stage of PD that affected persons begin to require assistance and that spouses begin progressively to assume their caregiver role (Bogard, 2010).…”
mentioning
confidence: 99%